Diseño, modelación y evaluación de un sistema de refrigeración por absorción usando energía térmica solar (2017)
"This work exposes the process of design, modeling and evaluation of an absorption refrigeration system using thermal solar energy. The project begins with the state of the requirements of the system based on the conditioning of spaces and with the definition the system operational demands depending of the user needing and his environment, social and economic conditions. Subsequently, it determinates the thermodynamics states required in each stage of the cycle, the refrigerant fluid properties and the characteristic operations of the equipment. With this information, it's possible the calculations of the cooling capacity and coefficient of performance how a way to characterize this design. These values are important because let the direct comparison between other similar devices." -- Tomado del Formato de Documento de Grado.